ANALISIS PENGARUH BRAND IMAGE, KETERLIBATAN PRODUK DAN MEDIA PERIKLANAN ES KRIM MAGNUM TERHADAP PERILAKU PEMBELIAN KONSUMEN - Cyntia Dewi; Suliyanto Suliyanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
The purpose of this research was to analyze the influence of brand image, product involvement and advertising media toward consumer purchase behavior. Accidental sampling was applied to get 100 respondents. By using Multiple Regression this study found that brand image, product involvement and advertising media had positive effect on consumer purchase behavior.